Continuidades y emergencias de acciones colectivas rurales en Colombia - Flor Edilma Osorio Pérez (Amnis)
Rural struggles in Colombia have developed amidst a complex scenario marked by a lengthy war that affects and transforms these communities, while their issues and visions of what the country should be are rendered invisible from within the centres of power. Throughout these historical dynamics, the rural inhabitants express their capacity to persist and resist in diverse ways, reinventing collective actions in face of old and new challenges and threats that are inscribed as relevant political practices at multiple scales. “What have been the continuities and emerging aspects of these collective actions?” is the question that orients this article, exploring diverse pasts and presents which dialogue with potential futures of the post accord period with the FARC.